Economic outlook: Navigating narrow paths - Jack Meaning (Institute for Fiscal Studies (IFS), 2025)
Ahead of the Autumn Budget, the UK economy stands at a pivotal juncture, with growth decelerating, unemployment rising and inflation above target.
Keywords: 330; Business and investment; Consumption and prices; Employment and income; Government finances and spending; Savings; pensions and wealth; Taxes and benefits; Productivity; Public finance; Tax